EFFECT OF WIKI AS A TEACHING TOOL ON CRITICAL THINKING AND PERFORMANCE LEVEL OF KATA EMPI IN KARATE FOR UNIVERSITY STUDENTS - Ahmed Almahallawy; Eman Almahallawy; Shady Fathalla (Sport şi Societate)
The current study aimed to identify the effect of WIKI as a teaching tool on the development of critical thinking and the level of kata Empi performance among karate Youth. and that is through designing a wiki space using participatory web editors to identify their impact on developing the level of kata Empi performance and critical thinking among karate Youth. Sample from the youth of Al-Arish Sports Club under (16) years old, and it consisted of (20 youths) representing a percentage (87%) of the research community as the basic research sample, and they were divided into two groups, one of which was experimental and consisted of (10 youth). and a control group consisting of (10 youth), and the exploratory study was conducted on a sample of (6 youth) representing a percentage (23%), to conduct the scientific transactions for the tests under discussion, and the researcher excluded the players who mastered the performance of kata (Empi) and their number reached (4 youth). Statistical analyses showed that: Significant Difference between the experimental group and control group in cognitive achievement, critical thinking, and the level of skill performance of Kata Empi for post-tests to the experimental group.Under the conditions of our article, the researcher’s conclusion that:the use of participatory web editors increases cognitive achievement; the method of explanation and presentation affects the level of skilful performance of kata Empi; the use of participatory web editors has a significant impact on improving the level of skill performance.